An in-tether sulfoxide chiral center influences the biophysical properties of the N-capped peptides. Issue 6 (15th March 2017) - Li, Jingxu; Tian, Yuan; Wang, Dongyuan; Wu, Yujie; Ye, Xiyang; Li, Zigang
Graphical abstract: Abstract: Thanks to their large binding interfaces, peptides are attractive ligands targeting protein-protein interactions compared with small molecules. Various strategies to improve peptides' pharmaceutical properties have been developed to constrain peptides into their functional three-dimensional structures. In our previous work, we reported that an in-tether chiral center could modulate peptides' biophysical properties. Herein, we applied this concept to construct a chiral sulfoxide center into the N-terminal end-cap system. We proved that this in-tether sulfoxide chiral center influences the structure of this N-capped template. In addition, longer peptides targeting estrogen receptor were also synthesized and we revealed that this chiral center could also modulate binding affinity to estrogen receptor alpha with enhanced protease resistance.